2015
DOI: 10.1158/1055-9965.epi-15-0038-t
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Coffee Drinking with Systemic Immune and Inflammatory Markers

Abstract: Background Coffee drinking has been inversely associated with mortality as well as cancers of the endometrium, colon, skin, prostate, and liver. Improved insulin sensitivity and reduced inflammation are among the hypothesized mechanisms by which coffee drinking may affect cancer risk; however, associations between coffee drinking and systemic levels of immune and inflammatory markers have not been well characterized. Methods We used Luminex bead-based assays to measure serum levels of 77 immune and inflammat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 52 publications
(95 reference statements)
7
45
2
Order By: Relevance
“…Further, a recent study has reported an inverse association between coffee consumption and the levels of different systemic immune and inflammatory markers (Loftfield et al, 2015). Coffee contains hundreds of compounds, many of which are biologically active, and the beneficial effect may be because of synergism of multiple agents.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent study has reported an inverse association between coffee consumption and the levels of different systemic immune and inflammatory markers (Loftfield et al, 2015). Coffee contains hundreds of compounds, many of which are biologically active, and the beneficial effect may be because of synergism of multiple agents.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is consumed mainly due to its stimulating and psychoactive effects as it affects brain function and behaviour. Several experimental studies have established that caffeine exhibit therapeutic effects against cardiovascular diseases, [2] inflammation, [3] including memory impairment and cognitive disorders such as dementia and Alzheimer's disease. [4,5] Furthermore, research has also shown the link between consumption of caffeine and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in proteomics methodologies provide an opportunity to move the field of coffee research forward . Indeed, using population‐based genomic, metabolomic and broad multi‐marker analyses, we and others have discovered novel and biologically plausible pathways correlated with habitual coffee consumption . In the current study, we aimed to further the understanding of downstream effects of coffee intake in humans using a highly sensitive and specific proteomics assay to identify habitual coffee‐induced changes of up to 80 protein markers associated with CVD in three Swedish large population‐based cohorts, the Prospective Study of the Vasculature in Uppsala Seniors (PIVUS), Uppsala Longitudinal Study of Adult Men (ULSAM) and EpiHealth.…”
Section: Introductionmentioning
confidence: 99%